(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
First of all the nanoparticles, they are materials so small that the human mind may not perceive them when thinking about their size, so that their size may reach [1-100 nm]. Modern studies have classified them according to their shapes, size and characteristics, and they include many categories for example fullerenes and ceramic NPs and metal NPs in addition to polymeric NPs. It has unique and distinctive properties, whether from the physical or chemical side, due to its precise nanoscale size and high surface area, and this makes it different and distinctive colors in the visible region due to its different absorption. It is logical that its distinctive shape, unique size and structure in general affect its properties, interactions, toughness and strength, and for these reasons it has become a frequent use in our life, especially from the domestic and commercial side, as its role in monitoring the environment as well as the medical and therapeutic field is clearly visible. Nanotechnology is science manage plan creation and utilizations of structures and gadgets or frameworks by controlling size and shape at nanoscale additionally it is the way toward comprehension and control of issue at measurement proximatly (1-100 nanometers).